Tracing surface and ground water with stable isotopes in a small permafrost research catchment - Lebedeva Liudmila (E3S Web of Conferences, 2019)
The study aims at assessing groundwater contribution to the streamflow at the small permafrost Shestakovka river watershed in Central Yakutia. Water from stream, lakes, snow, rain, surface flow and suprapermafrost groundwater is characterized by specific isotopic signature. At least one third of the spring flood is formed by “old” pre-event water as showed by mixing model based on stable isotopes as tracers. Presence of talik aquifers associated with sandy hills covered by pine forest suggests that talik groundwater could be an important source of streamflow at the small river basin in continuous permafrost.